Developments and Applications of Liver-on-a-Chip Technology—Current Status and Future Prospects - Joseph Mugaanyi; Jing Huang; Jiongze Fang; Arthur Musinguzi; Caide Lu; Zaozao Chen (Biomedicines)
Background/Objectives: Liver-on-a-chip (LiOC) technology is increasingly recognized as a transformative platform for modeling liver biology, disease mechanisms, drug metabolism, and toxicity screening. Traditional two-dimensional (2D) in vitro models lack the complexity needed to replicate the liver’s unique microenvironment. This review aims to summarize recent advancements in LiOC systems, emphasizing their potential in biomedical research and translational applications. Methods: This narrative review synthesizes findings from key studies on the development and application of LiOC platforms. We explored innovations in material science and bioengineering, including microfluidic design, 3D printing, stem cell– and tissue-derived liver organoid integration, and co-culture strategies. Commercially available LiOC systems and their regulatory relevance were also evaluated. Results: LiOC systems have evolved from simple PDMS-based chips to complex, multicellular constructs incorporating hepatocytes, endothelial cells, Kupffer cells, and hepatic stellate cells. Recent studies demonstrate their superior ability to replicate liver-specific architecture and functions. Applications span cancer research, drug toxicity assessment (e.g., drug-induced liver injury prediction with >85% sensitivity), disease modeling, and regenerative medicine. Several platforms have gained FDA recognition and are in active use for preclinical drug testing. Conclusions: LiOC technology offers a more physiologically relevant alternative to traditional models and holds promise for reducing reliance on animal studies. While challenges remain, such as vascularization and long-term function, ongoing advancements are paving the way toward clinical and pharmaceutical integration. The technology is poised to play a key role in personalized medicine and next-generation therapeutic development.